Female Brain and Endocrinological Research–Veteran (FemBER-Vet) study: A study protocol for identifying endocrinological, lifestyle and psychosocial determinants of brain health outcomes in female veterans for future intervention success - Tamlyn Watermeyer; Elliott Atkinson; Glyn Howatson; Gill McGill; Christina Dodds; Paul Ansdell; Chinedu Udeh-Momoh (PLoS ONE, 2025)
Background Recent studies have demonstrated a greater risk of dementia in female veterans compared to civilians; with the highest prevalence noted for former service women with a diagnosis of psychiatric (trauma, alcoholism, depression), and/or a physical health condition (brain injury, insomnia, diabetes). Such findings highlight the need for increased and early screening of medical and psychiatric conditions, and indeed dementia, in the female veteran population. Further, they call for a better understanding of the underlying biopsychosocial mechanisms that might confer heightened risk for female veterans, to tailor preventative and interventional strategies that support brain health across the lifespan. Methods The Female Brain and Endocrinological Research–Veteran (FemBER-Vet) Study will create a highly-phenotyped readiness cohort of ex-service persons as well as non-veterans to assess the impacts of, and risks associated with, military service on brain health, using state-of-the-art non-invasive cognitive, physiological and biomarker capture techniques. FEMBER-Vet will include 90 participants across three study groups (30 female veterans, 30 male veterans, 30 female civilians) to delineate the precise biological, socio-demographic, health, lifestyle, military-related, and life-course determinants of brain health outcomes (psychosocial, cognitive, neurophysiological, and other biomarkers). Discussion This work addresses the poorly understood biopsychosocial outcomes that female veterans experience compared to their male counterparts and the general female population. Ultimately, it will provide evidence to support the development of tailored interventions for an emerging health priority that currently lacks sufficient evidence for screening and therapeutic intervention.